Analisis Kasus Pelanggaran Etika Bisnis PT Megasari Makmur Pada Produk Obat Nyamuk HIT Berbahaya - Nadhila Nuraini; Eliana Ratmawati; Dinda Vanya Oktaviani; Mohammad Zein Saleh (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2025)
The mosquito repellent product brand HIT, which is suspected of containing harmful active substances, has become the subject of a business ethics violation by PT Megasari Makmur and is the main focus of this analysis. This study aims to examine the elements that led the company to violate business ethics, the importance of regulations governing the use of chemicals, and the impact of such violations on the company's reputation and consumer trust. Data were obtained through literature review and thematic analysis using a qualitative descriptive approach. The findings indicate that non-compliance with business ethics regulations not only harms consumers but also threatens the company's sustainability. In response, PT Megasari Makmur has recalled the problematic product and is working to improve the formulation to make it safer. This study recommends the importance of transparency and ongoing internal audits to ensure compliance with safety standards and maintain consumer trust in the future.